(untitled) (Research, Society and Development, 2022)
Vitamins and minerals, collectively known as micronutrients, are essential elements for the survival of organisms due to their vital role in maintaining the bodies homeotic. Ascorbic acid, commonly known as vitamin C, is an important water-soluble antioxidant micronutrient involved in regulating several gene expressions. Tablets and capsules may release their contents minutes after ingestion; these are immediate release formulations. The objective of this study is to produce and verify the theoretical average weight of different formulations of capsules containing vitamin C associated with carboxymethylcellulose as a pre-evaluation of a modified release formulation. The production took place in the manipulation laboratory of the Pharmacy-School of the UniEvangélica University, located in Anapolis-GO. After the preparation of the capsules, these were weighed to obtain the average weight, which was 197 mg. The statistical values are within the acceptance range recommended by the pharmacopoeia, which establishes that the maximum value allowed for the relative standard deviation is 4%, so the manipulation process met the established requirements. The results of the study demonstrated that it is feasible to continue with further tests to verify the adequacy of the formulations to a modified release pattern.